2002
DOI: 10.1002/app.10999
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectra of high‐density, low‐density, and linear low‐density polyethylene pellets and prediction of their physical properties by multivariate data analysis

Abstract: Raman spectra have been measured for pellets of five samples of high-density polyethylene (HDPE), seven samples of low-density polyethylene (LDPE), and six samples of linear low-density polyethylene (LLDPE). The obtained Raman spectra have been compared to find out characteristic Raman bands of HDPE, LDPE, and LLDPE. Principal component analysis (PCA) was applied to the Raman spectra in the 1600 -650 cm Ϫ1 region after multiplicative scatter correction (MSC) to discriminate the Raman spectra of the three diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(72 citation statements)
references
References 89 publications
(116 reference statements)
4
66
0
2
Order By: Relevance
“…2D spectroscopy was mentioned in the NIR study of LLDPE [295]. Sato et al [296] mentioned 2D correlation in their Raman study of polyethylene. Zhang et al [297] carried out dielectric spectroscopy of the miscible blend of PVPh and PEMA.…”
Section: Citations In Other Fieldsmentioning
confidence: 99%
“…2D spectroscopy was mentioned in the NIR study of LLDPE [295]. Sato et al [296] mentioned 2D correlation in their Raman study of polyethylene. Zhang et al [297] carried out dielectric spectroscopy of the miscible blend of PVPh and PEMA.…”
Section: Citations In Other Fieldsmentioning
confidence: 99%
“…However, the band at 1300-1296 cm À1 can probably be assigned to the twisting vibration of the CH 2 group which appears in the region [38,39]. For the aliphatic series of (CH 2 ) n , the intensity of the band at 1305-1295 cm À1 increases with n [38] and, in addition, the Raman spectra of polyethylenes show a strong peak in this area [42,43]. The signal at 1300-1296 cm À1 may thus mainly be due to methylene bridges formed between phenolic species in the condensation reactions.…”
Section: Online Monitoring Of Synthesis Of Phenol-formaldehyde Resol mentioning
confidence: 99%
“…[34 -36] Actually, recent studies have demonstrated the usefulness of the Raman fingerprint region for the quantitative analysis of PE crystallinity. [29,31,33] All the spectra were recorded under back-scattering conditions with 5 cm −1 spectral resolution using the 488-nm line of an Ar laser (Innova Coherent 70) with a power of about 10 mW. The detector was a charge coupled device (CCD) from Princeton Instruments Inc. cooled to 160 K.…”
Section: Micro-raman Crystallinity Measurements On the Acetabular Cupsmentioning
confidence: 99%